The XRE Family Transcriptional Regulator SrtR in Streptococcus suis Is Involved in Oxidant Tolerance and Virulence - Hu, Yuli; Hu, Qian; Wei, Rong; Li, Runcheng; Zhao, Dun; Ge, Meng; Yao, Qing; Yu, Xinglong (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus suis is a zoonotic pathogen that harbors anti-oxidative stress genes, which have been reported to be associated with virulence. Serial passage has been widely used to obtain phenotypic variant strains to investigate the functions of important genes. In the present study, S. suis serotype 9 strain DN13 was serially passaged in mice 30 times. The virulence of a single colony from passage 10 (SS9-P10) was found to increase by at least 140-fold as indicated by LD50 values, and the increased virulence was stable for single colonies from passage 20 (SS0-P20) and 30 (SS0-P30). Compared to the parental strain, the mouse-adapted strains were more tolerant to oxidative and high temperature stress. Genome-wide analysis of nucleotide variations found that reverse mutations occurred in seven genes, as indicated by BLAST analysis. Three of the reverse mutation genes or their homologs in other bacteria were reported to be virulence-associated, including ideSsuis in S. suis, a homolog of malR of Streptococcus pneumoniae, and a homolog of the prepilin peptidase-encoding gene in Legionella pneumophila. However, these genes were not involved in the stress response. Another gene, srtR (stress response transcriptional regulator), encoding an XRE family transcriptional regulator, which had an internal stop in the parental strain, was functionally restored in the adapted strains. Further analysis of DN13 and SS9-P10-background srtR-knock-out and complementing strains supported the contribution of this gene to stress tolerance in vitro and virulence in mice. srtR and its homologs are widely distributed in Gram-positive bacteria including several important human pathogens such as Enterococcus faecium and Clostridioides difficile, indicating similar functions in these bacteria. Taken together, our study identified the first member of the XRE family of transcriptional regulators that is involved in stress tolerance and virulence. It also provides insight into the mechanism of enhanced virulence after serial passage in experimental animals.